PENGARUH DISIPLIN KERJA, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PERKEBUNAN SUMATERA UTARA - Tanjung, Hasrudy (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
This study aims to determine whether there is influence of labor discipline against the employee satisfaction, Is there any effect of competence on employee satisfaction, Is there any influence of organizational culture on employee satisfaction, Is there any influence of labor discipline of organizational culture and Is there any influence between labor discipline competence and organizational culture on job satisfaction of employees at the Plantation Office of North Sumatra Province.The population in this study were all employees remain on duty Plantation North Sumatra Province which amounted to 130 people. Sample study determined using census sampling or sampling techniques that saturated the entire study population sampled. Data were analyzed using path analysis model, classic assumption test and parameter estimation and hypothesis testing.Work discipline against the employee satisfaction has a positive and significant impact, competencies on job satisfaction of employees have a positive and significant impact. Organizational culture on employee satisfaction has a positive and significant impact thus organizational culture needs to be preserved and enhanced back. Labor discipline of organizational culture on the Plantation Office of North Sumatra province has positive and significant impact. Labor discipline and competence through organizational culture on job satisfaction of employees at the Plantation Office of North Sumatra province has a positive and significant influence, and thus the discipline of work and competence through organizational culture needs to be preserved.Keywords: Work Discipline, Competence, Organizational Culture and Employee Job Satisfaction